Model zarządzania i organizacja systemu oświaty w latach 1996-2012 na przykładzie gminy Krynica-Zdrój - Jarecki, Grzegorz (My University, 2012)
Niniejsza praca porusza zagadnienia związane z procesem zarządzania finansami publicznymi i ich wpływem na system zatrudnienia w jednostkach działających z zakresie oświaty. Wskazuje na powiązania miedzy tymi elementami i ich wzajemnymi korelacjami. Praca przedstawia zmiany jakie dokonują się w gminie pod wpływem demografii i jaki to ma wpływ na subwencję oświatową. Dodatkowo praca została wzbogacona o warianty naprawcze w gminnej sieci szkolnej.

This thesis brings up the issue connected with the process of the management of the public finances and their influence on the employment system in units functioning within education field. Moreover, it points to connections between these elements and their mutual correlations. The study presents the changes that occur in the district under the influence of the demography and what influence it has on the education subsidy. What is more, the thesis was enriched with repair variants in the district school network.
The model of management and organisation of the education system between 1996-2012 based on the example of the district of Krynica-Zdrój
Keywords: finanse publiczne; zarządzanie; oświata; zatrudnienie; finansowanie oświaty; gmina